Influencia del nivel de conocimiento de la gestión de RSE de la fundación BBVA Continental en el posicionamiento en el cliente del BBVA Banco Continental - Trujillo 2016 - Sánchez Campero, Renzo Arturo (2017)
This investigation has been elaborated with the purpose of determine the level of influence of the level of knowledge of the management of corporate social responsibility applied by the BBVA Fundation in the positioning in the client of the BBVA Banco Continental. This report has been developed with a transactional research design or transversal - Descriptive: applied. The data collection technique used was the survey, with the purpose of applying it to the clients of the BBVA Banco Continental. After developing the research, with all the established process, can conclude that, by hypothesis testing, the influence of the level of knowledge of corporate social responsibility management used by the BBVA Continental Foundation in the positioning of the BBVA Banco Continental client in the district of Trujillo - 2016, is significant. According to the analysis of results of the surveys applied can be seen that the influence is positive, of strong degree. The research hypothesis was tested, by means of the statistical test Tau-b of Kendall at a level of significance of 5% and with a sample of 383 clients. The present investigation will serve as a guide for BBVA Banco Continental, as well as, for the BBVA Continental Foundation; with which they can analyze the level of knowledge of the management of corporate social responsibility of clients and the positioning that BBVA Continental has in them, in this way, make the improvements they think are convenient.